Flt3/Flt3L Participates in the Process of Regulating Dendritic Cells and Regulatory T Cells in DSS-Induced Colitis - Jing-Wei Mao; Yu-Shuang Huang; Hai-Ying Tang; Jian Bi; Yan-Fei Liu; Ying-De Wang (Gastroenterology Research and Practice)
The immunoregulation between dendritic cells (DCs) and regulatory T cells (T-regs) plays an important role in the pathogenesis of ulcerative colitis (UC). Recent research showed that Fms-like tyrosine kinase 3 (Flt3) and Flt3 ligand (Flt3L) were involved in the process of DCs regulating T-regs. The DSS-induced colitis model is widely used because of its simplicity and many similarities with human UC. In this study, we observe the disease activity index (DAI) and histological scoring, detect the amounts of DCs and T-regs and expression of Flt3/Flt3L, and investigate Flt3/Flt3L participating in the process of DCs regulating T-regs in DSS-induced colitis. Our findings suggest that the reduction of Flt3 and Flt3L expression may possibly induce colonic immunoregulatory imbalance between CD103+MHCII+DCs and CD4+CD25+FoxP3+T-regs in DSS-induced colitis. Flt3/Flt3L participates in the process of regulating DCS and T-regs in the pathogenesis of UC, at least, in the acute stage of this disease.